Влияние структуры на диффузию и накопление водорода в сплаве Zr-1Nb; Известия вузов. Физика; Т. 65, № 8 - Грабовецкая Г. П. Галина Петровна; Степанова Е. Н. Екатерина Николаевна; Никитенков Н. Н. Николай Николаевич; Мишин И. П. Иван Петрович; Винокуров В. А. Владимир Алексеевич; Сыпченко В. С. Владимир Сергеевич; Кудияров В. Н. Виктор Николаевич (2022, 2022)
Заглавие с экрана